Analisis Kendala Guru dalam Menerapkan Kurikulum Merdeka Belajar di Sekolah Dasar (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This research aims to identify and analyze the primary constraints faced by Primary School (SD) teachers in effectively implementing the Merdeka Curriculum (KM). KM implementation, which emphasizes student-centered learning and the Pancasila Student Profile Strengthening Project (P5), demands significant changes in the teachers' teaching paradigm. This study utilizes a qualitative approach with a descriptive-analytical method. Data were collected through in-depth interviews with 15 classroom teachers, observation of learning activities, and documentation studies across three primary schools implementing KM independently. The findings reveal that the main constraints can be classified into two categories: pedagogical competency constraints and managerial/structural constraints. Pedagogical constraints include a lack of in-depth understanding of the P5 concept and difficulties in designing assessment oriented toward differentiation. Meanwhile, managerial constraints encompass the high administrative load related to the preparation of flexible Teaching Modules (Modul Ajar), as well as limited time allocated for professional development and inter-teacher collaboration. The implications of these findings suggest the necessity of improving the quality of practical training, providing continuous mentoring (coaching), and simplifying the administrative burden so that teachers can focus on the essence of differentiated learning and P5 projects.